Alerting relatives about heritable risks: the limits of confidentiality. (5th April 2018) - Lucassen, Anneke; Gilbar, Roy
Abstract : Are there situations when sharing a patient's genetic information with relatives without consent is acceptable? Anneke Lucassen and Roy Gilbar discuss